Evaluating the energy consumption of adaptation tasks for a CPS in the Arctic Tundra - Omond, Antoine Stephane Pierre Guy; Rais, Issam; Coullon, Hélène (IEEE, 2024)
Cyber-Physical Systems deployed in scarce resource environments like the Arctic Tundra (AT) face extreme conditions. Nodes deployed in such environments have to carefully manage a limited energy budget, forcing them to alternate long sleeping and brief uptime periods. During uptimes, nodes can collaborate for data exchanges or computations by providing services to other nodes. Deploying or updating such services on nodes requires coordination to prevent failures (e.g., sending new/updated API, waiting for service activation/deactivation, etc.). In a CPS with short uptime periods, such coordination can be energy-consuming due to low opportunities for communications.This paper evaluates and studies nodes’ energy consumption during deploy or update tasks coordination according to different CPS configurations (i.e., number of nodes, uptime duration, radio technology, or relay node availability). Results show high energy consumption in scenarios where nodes wake up specifically to deploy/update. It is shown that it is beneficial to do adaptation tasks while overlapping with existing uptimes (i.e., reserved for observation activities).This paper also evaluates and studies how nodes’ uptime duration and relay node availability influence energy consumption. Increasing uptime duration can reduce energy consumption, up to 12%. Using an available relay node for communication reduces the energy consumption by 47% to 99%.